GAMBARAN FAKTOR PERSONAL YANG MELATARBELAKANGI TINDAKAN PENCEGAHAN PENULARAN HIV/AIDS PADA WARGA BINAAN DENGAN HIV POSITIF (Studi Kualitatif di Lembaga Pemasyarakatan Wanita Klas IIA Kota Semarang) - Galuh Ajeng Pangestika; Lintang Dian Saraswati; Mateus Sakundarno Adi (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Preventive action is a way to break the chain of transmission of HIV / AIDS. It is very necessary to reduce the high incidence of HIV, especially to prisoners in Indonesia.This research aimed to describe the factors that underlying precaution transmission of HIV/AIDS in prisoners with HIV-positive. The explorative study used qualitative approach. There were 10 subjects joined in depth interview. Triangulation was done by health workers and prison officers. Data reliability used auditing with flow analysis of inspection data. The results showed that subjects are taking action to prevent HIV/AIDS with good covering prevention of transmission of HIV to others. This is because the subjects had good knowledge and attitudes about HIV/AIDS. Suggestion for the prison is to increase information about HIV/ AIDS in prisons with counseling for all prisoners.